JUNIOR HIGH SCHOOL TEACHERS’ EXPERIENCES IN INTERPRETING DIGITAL COMPETENCE, WELL-BEING, AND ORGANIZATIONAL SUPPORT IN BUILDING PERFORMANCE RESILIENCE (A PHENOMENOLOGICAL STUDY IN BALIKPAPAN CITY) (International Journal of Cultural and Social Science, 2026)
The digital transformation of education requires teachers to develop digital competence, maintain well-being, and receive organizational support in order to build sustainable performance resilience. This study aims to explore how junior high school teachers in Balikpapan City interpret digital competence, well-being, and organizational support in shaping their resilience and professional performance. This research used a qualitative approach with a phenomenological method. The study was conducted at SMP Negeri 6 Balikpapan and SMP Patra Dharma 1 Balikpapan. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using phenomenological stages, including bracketing, horizontalization, identification of meaning units, clustering of themes, textural description, structural description, and synthesis of essence. The findings show that teachers interpret digital competence as a strategic professional capacity that supports evidence-based decision-making, learning innovation, communication, collaboration, content creation, and digital security. Teacher well-being, including physical, psychological, and social dimensions, strengthens focus, energy, emotional stability, creativity, and work consistency. Organizational support through appreciation, feedback, facilities, professional development, and social attention increases motivation, dedication, professionalism, and psychological resilience. The integration of digital competence, well-being, and organizational support forms adaptive performance resilience, enabling teachers to remain innovative, productive, and professionally consistent in facing curriculum pressure, technological change, and pedagogical demands.